Study on sentinel hosts for surveillance of future COVID-19-like outbreaks - Li, Yanjiao; Hu, Jingjing; Hou, Jingjing; Lu, Shuiping; Xiong, Jiasheng; Wang, Yuxi; Sun, Zhong; Chen, Weijie; Pan, Yue; Thilakavathy, Karuppiah; Feng, Yi; Jiang, Qingwu; et al. (Springer Science and Business Media LLC, 2024)
The spread of SARS-CoV-2 to animals has the potential to evolve independently. In this study, we distinguished several sentinel animal species and genera for monitoring the re-emergence of COVID-19 or the new outbreak of COVID-19-like disease. We analyzed SARS-CoV-2 genomic data from human and nonhuman mammals in the taxonomic hierarchies of species, genus, family and order of their host. We find that SARS-CoV-2 carried by domestic dog (Canis lupus familiaris), domestic cat (Felis catus), mink (Neovison vison), and white-tailed deer (Odocoileus virginianus) cluster closely to human-origin viruses and show no differences in the majority of amino acids, but have the most positively selected sites and should be monitored to prevent the re-emergence of COVID-19 caused by novel variants of SARS-CoV-2. Viruses from the genera Panthera (especially lion (Panthera leo)), Manis and Rhinolophus differ significantly from human-origin viruses, and long-term surveillance should be undertaken to prevent the future COVID-19-like outbreaks. Investigation of the variation dynamics of sites 142, 501, 655, 681 and 950 within the S protein may be necessary to predict the novel animal SARS-CoV-2 variants.